PELATIHAN PENGELOLAAN PANGAN BERBASIS ORGANIK DALAM MENUNJANG AGROEKOWISATA DI KOTA DENPASAR - Sukanteri, Ni Putu; Tamba , I Made; Amaral , Ni Putu Anglila; Arisandhi, I Made Dimas (JURNAL PENGABDIAN PAPUA, 2023)
Agrotourism is a tourist attraction that relies on agriculture for tourist visits. The use of nature around the farm is designed in such a beautiful way as to provide an attraction for people to visit. And crossing agricultural areas with the hope of giving its own impression as an experience that can be seen by visitors. The purpose of the service is carried out in an effort to increase the knowledge, skills and income of farmer groups involved as agrotourism objects in Denpasar City. Activities are carried out through direct assistance and training at agrotourism locations in the city of Denpasar. Service activities result in the implementation of socialization, carried out in an effort to create changes in the knowledge of agrotourism actors to increase various outputs such as products and income. Training is carried out to improve the skills of agrotourism managers and actors so they are able to provide interesting experiences for agrotourism visitors. Assistance is provided so that the training provided continues to be implemented so that it is able to change the knowledge, skills and income of agrotourism actors in Subak Sembung, Denpasar City. Keywords: Agrotourism, Food, Organic farm